Aplikasi Persediaan Sparepart Mesin Berbasis Web Pada PT. Giesecke And Devrient Indonesia - Mia Rosmiati (Universitas Bina Sarana Informatika, 2018)
The use of information technology in processing a company's data is a very important part. With the existence of an information technology data processing to be very fast, precise, and accurate in generating an information. PT. Giesecke And Devrient Indonesia is a company engaged in the distribution of money sorting machine and machine spare parts sales. In data processing PT. Giesecke And Devrient Indonesia still use manual system, so the information produced less than the maximum. Data processing which still using manual system become constraint which must be faced by PT. Giesecke And Devrient Indonesia, especially the process of inventory data processing machine spare parts in the warehouse. The warehouse has the responsibility in managing the machine spare parts in and out of the warehouse and also responsible for making reports on the availability of spare parts in the warehouse. Therefore, PT. Giesecke And Devrient Indonesia tries to develop an information system that will be used in spare part inventory data processing. With this information system is expected to assist users in presenting a information needed by the company quickly, precisely, and accurately. In this research will be designed a web-based inventory application using waterfall method as the method of software development.Keywords: Information, Inventory, System